ANALISIS YURIDIS TERHADAP PERJANJIAN PENGIKATAN JUAL BELI (PPJB) UNIT APARTEMEN SEBAGAI AGUNAN DALAM PERJANJIAN KREDIT INVESTASI (STUDI DI PT.BANK NATIONALNOBU TBK) - MELDA NEHEMIA SITINJAK (PREMISE LAW JURNAL, 2016)
A loan agreement requires collateral as warranty for repayment. The object bound as collateral in the Loan Agreement between PT. Bank Nationalnobu Tbk and PT. ITC Multifinance is a PPJB (Binding agreement for sale and purchase). The PPJB bound as collateral is the PPJB of Grand Kartini Apartment Units made between PT. Internusa Jaya Semesta as the developer and the buyer as referred to Article 10 of Loan Agreement of PT. Bank Nationalnobu Tbk and PT ITC Multifinance. This research was expected to be able to resolve the problems concerning the responsibilities of PT. Internusa Jaya Semesta as the developer in the PPJB in case of default, the legitimacy of the PPJB as collateral in the investment loan agreement between PT. Bank Nationalnobu Tbk and PT. ITC Multifinance, and the legal consequence and protection toward PT. Bank Nationalnobu Tbk if the developer cannot continue the construction of the apartment units when a force majeure event occurs after the loan signing. The results show that if PT. Internusa Jaya Semesta (the developer) defaults, it is responsible for the payment of fines, interests, and for the repair of any physical damage on the apartment. The collateral binding i.e. apartment units, based on the PPJB in the Investment Loan Agreement between PT. Bank Nationalnobu Tbk and PT. ITC Multifinance, is void. PT. Bank Nationalnobu Tbk does not obtain any legal protection at all from the binding of PPJB as collateral. Keywords: PPJB (Binding agreement for sale and purchase), Investment Loan, Force Mejeure